Evaluation of the Functional Status of the Respiratory System in Students - Kurbanov A.Sh; Dustov K.T; Sagatov H.Q (Global Scientific Publishing, 2023)
The article is devoted to the study of the problems of ensuring the normal functioning of the students` body and protecting their health. For this purpose, the functional activity of the respiratory organs was assessed in this population. The study used generally accepted methods for studying the activity of the respiratory system with the determination of capacitive and volumetric indicators of the respiratory system
Keywords: physiological; activity; respiratory; ensuring